2009
DOI: 10.1002/mde.1466
|View full text |Cite
|
Sign up to set email alerts
|

The determinants of industry concentration: two new empirical regularities

Abstract: This paper reports two new empirical regularities relating to industry concentration.First, concentration levels closely correlate in related industries. Second, the correlation is moderated by the degree of relatedness between the industries. These regularities are derived from the Trinet database, using a survivor-based measure of relatedness. We argue that these previously overlooked relations may be explained in terms of 1) "spillover effects" between industries and 2) lifecycle factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Time. Time and evolution are noted in various studies on market concentration and competition (e.g., Lien & Foss, 2009;Lusch & Laczniak, 1987;Mia, 2018). Based on a life cycle perspective, Klepper and Graddy (1990) suggested that the competition in nascent, or emergent, industries tends to be fiercer compared to relatively more mature markets.…”
Section: Market Share Instabilitymentioning
confidence: 99%
“…Time. Time and evolution are noted in various studies on market concentration and competition (e.g., Lien & Foss, 2009;Lusch & Laczniak, 1987;Mia, 2018). Based on a life cycle perspective, Klepper and Graddy (1990) suggested that the competition in nascent, or emergent, industries tends to be fiercer compared to relatively more mature markets.…”
Section: Market Share Instabilitymentioning
confidence: 99%
“…Hence, the signifi cance of industrial structure and development induces scholars to perform the deeper research on how the potential of industrial sectors contributes to the advancement of economic performance. Different sets of factors are addressed in the scientifi c literature as a part of industrial structure analysis -some studies highlight the composition of industry with reference to the level of technology intensity (Carrol et al, 2000;Hatzichronoglou, 1997), others introduce the assessment of the competitive environment based on the fi ve-force model provided by Porter (1980), a part of the studies are developed for the analysis of the value-chain (Porter, 1985;Shank et al, 1992), industry concentration (Lien & Foss, 2009;Bos & Jalil, 2006) or the assessment of the impact of international competition and innovation. The latter factors are considered to be the main determinants that force constant changes in manufacturing industries, although the research on the other economic and non-economic factors that could shape the industrial structure is available.…”
Section: Literature Reviewmentioning
confidence: 99%
“…From an industry perspective we may also note that some industries are not very closely related to any other industries, while still other industries are closely related to several. By means of an analogy; some industries have several close neighbors, and others do not (Santalo & Becerra, 2008;Lien & Foss, 2009). Also, some industries are related to fragmented industries, while other industries are related to concentrated industries (Scott, 1993).…”
Section: What Does Diversification Imply For Industry Structure and Imentioning
confidence: 99%